On the Jackson type inequality in the dyadic BMO space - I. P. Irodova (Моделирование и анализ информационных систем, 2009)
In this paper the direct theorem of the approximation theory for functions from the dyadic Besov space is proved. Together with the inverse theorem, it allows to solve an interpolation problem between dyadic BMO and the dyadic Besov space.